Mechanism of Mangosteen Shearing - Bundit Jarimopas,; Kulwadee A-sai,; Vimol Maneewatanaset, (Agriculture and Natural Resources, 1993)
This research is to determine a mechanism to shear mechanically a mangosteen fruit. The developed mechanism comprises a knife rotating to shear the mangosteen statistically placed. The knife made of metal handsaw blade of 5 different designs was tested . Two designs resulted very good shearing while 90 to 100% of perfect shearing was found.